2015
DOI: 10.1007/s10681-015-1534-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and cytometric analyses in artificial intercytotypic hybrids of the emergent orchid model species Erycina pusilla

Abstract: Erycina pusilla is considered a potential model organism for orchids, because of several advantageous features, such as short juvenile period, low chromosome number and all year round blooming. Two different chromosome numbers (2n = 10 and 2n = 12) are reported for E. pusilla, which suggests two cytotypes. To reveal the genome homology between these two cytotypes, we generated hybrids from the intercytotypic reciprocal crosses (2n = 10 9 2n = 12 and 2n = 12 9 2n = 10), and applied 4 0 ,6-diamidino-2-phenylindo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Their study confirmed earlier observations by Johnston et al (2005), who, after measuring the DNA content of 34 Brassicaceae species and sequencing the ITS region (internal transcribed spacer region of DNA between the small and large ribosomal RNA genes) for 23 taxa, had found that despite the evidence of species with decreases and increases in GS, including polyploidization, the evolution of this family's GS had a conservative nature. Polyploidy, and also dysploidy (an increase or decrease in chromosome number as a result of structural rearrangements) as mechanisms of genome evolution have been suggested for Ocimum, Orchidaceae, Bromeliaceae, Colchicum, and Iridaceae (Bory et al, 2008;Carović-Stanko et al, 2010;Rupp et al, 2010;Trávníček et al, 2011;Moraes et al, 2012Moraes et al, , 2015Jersáková et al, 2013;Fridlender et al, 2014;Gitaí et al, 2014;Yeh et al, 2015).…”
Section: Asparagusmentioning
confidence: 99%
“…Their study confirmed earlier observations by Johnston et al (2005), who, after measuring the DNA content of 34 Brassicaceae species and sequencing the ITS region (internal transcribed spacer region of DNA between the small and large ribosomal RNA genes) for 23 taxa, had found that despite the evidence of species with decreases and increases in GS, including polyploidization, the evolution of this family's GS had a conservative nature. Polyploidy, and also dysploidy (an increase or decrease in chromosome number as a result of structural rearrangements) as mechanisms of genome evolution have been suggested for Ocimum, Orchidaceae, Bromeliaceae, Colchicum, and Iridaceae (Bory et al, 2008;Carović-Stanko et al, 2010;Rupp et al, 2010;Trávníček et al, 2011;Moraes et al, 2012Moraes et al, , 2015Jersáková et al, 2013;Fridlender et al, 2014;Gitaí et al, 2014;Yeh et al, 2015).…”
Section: Asparagusmentioning
confidence: 99%
“…There is a series of multiple chromosome rearrangements required to generate the differences between the two karyotypes. Our previous result from Yeh et al (2015) as well as our subsequent efforts also showed no evidence so far for fertile F1 hybrids between the parents with the two different karyotypes. The sterile F1 hybrids and our findings in the study support the hypothesis that these are two separate species, not just cytotypes.…”
Section: Two Cytotypes or Different Species?mentioning
confidence: 58%
“…The two cytotypes of E. pusilla were collected from Ecuador (2n = 10) and from Surinam (2n = 12) and their specimens were deposited in the herbarium of Taiwan's National Museum of Natural Science (Yeh et al 2015). All plants were maintained and cultured on half-strength Murashige and Skoog medium (Murashige and Skoog 1962), and cultivated in growth chambers under long-day conditions (16-h photoperiod) at 22°C.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations